The dilemma of treating the infected versus the wounded: Gaza's healthcare system is choked. (1st July 2021) - Aamir, Alifiya; Awan, Hashir Ali; Diwan, Mufaddal Najmuddin; Kazmi, Syeda Kanza; Hasan, Mohammad Mehedi; Douba, Zain; Ullah, Irfan
Abstract: Gaza has been facing persistent disturbance since the last 14 years. Even before the pandemic, Gaza faced a dire healthcare consequence with prevalent instability, lack of adequate medical resources, and limited health‐related infrastructure. Gaza continued to struggle while responding to the pandemic as the other nearby countries. However, the challenges were compounded with the onset of the conflict that affected Gaza's infrastructure and displaced tens of thousands to make‐shift shelters. The testing capacity of Gaza is alarmingly low that makes any outbreak difficult to document. Additionally, all medical centres have been affected by the ongoing conflict. These centres, if not directly impacted, are severely overwhelmed with those injured during the conflict, shifting focus and resources away from coronavirus. Vaccinations in Gaza cover only 1.9% of the population and a great number of unvaccinated people now may act as vectors of transmission in overcrowded shelters. Furthermore, non‐availability of clean water to maintain hygienic conditions has heightened the risk of an explosive surge in cases. Hence, beyond the ceasefire, further steps need to be taken to strengthen Gazan response to COVID‐19 pandemic.